DISEASE MODIFYING ANTIRHEUMATIC DRUGS IN THE TREATMENT OF RHEUMATOID ARTHRITIS - Birol Balaban,; Kenan Tan,; Rıdvan Alaca, (Archives of Rheumatology, 2001)
At present, there is no cure for rheumatoid arthritis. Its medical management is aimed at relieving symptoms and slowing disease progression. The medical treatment of rheumatoid arthritis contains nonsteroidal anti-inflammatory drugs (NSAIDs) initially, followed by corticosteroids and disease-modifying antirheumatic drugs (DMARDs) introduced only when earlier measures have been proven ineffective. Lots of studies concerning combination use of disease-modifying antirheumatic drugs and their using time in the treatment of rheumatoid arthritis have been carried out for many years. In this article the place of disease-modifying antirheumatic drugs in therapy and developments about them will be reviewed and the drugs which have been developed spesifically for the treatment of rheumatoid arthritis recently and their usage will be discussed.